POISONING TRENDS IN PANCHKULA DISTRICT OF HARYANA STATE, INDIA (Journal of Forensic Medicine & Toxicology, 2015)
Poisoning has been a part of human history since the very beginning and even today poisoning is one of the major causes of deaths in India. In this study, the trend of poisoning was studied from January 2010 to December 2013 in the Department of Forensic Medicine in General Hospital, Sector 6, Panchkula Haryana. This study was undertaken to understand and draw any relevant connection between the trends of poisoning with respect to other personal and sociological factors. The total number of autopsies performed was 1247, out of which 88(27.06%) were that of a suspected poisoning. The total number of poisoning cases shows an increase from 2010 to 2013. Poisoning cases in males were more compared to that in females. Aluminium phosphide was most common poison in both males and females followed by alcohols in males and organophosphate in females.
Keywords: Poisoning; Aluminium Phosphide; Alcohols; Organophosphates